Thrombectomy with and without computed tomography perfusion imaging for large-vessel occlusion stroke in the extended time window: a meta-analysis of randomized clinical trials - Zhan, Zheng; Gu, Feng; Ji, Yi; Zhang, Yu; Ge, Yi; Wang, Zhong (Frontiers in Neurology, 2023)
Objective: In recent years, several studies have used computed tomography perfusion (CTP) to assess whether mechanical thrombectomy can be performed in patients with large vessel occlusive (LVO) strokes in the extended time window. Still, it has the disadvantage of being time-consuming and expensive. This study aims to compare the impact of the CTP group with the non-CTP group [non-contrast CT (NCCT) ± CT angiography (CTA)] on the prognosis of this population of patients mentioned above.Methods: A search of Pubmed, EMBASE, and Cochrane Library databases was conducted to collect randomized controlled trials (RCTs) comparing the two strategies. Outcome indicators and factors influencing prognosis were summarised by standardized mean differences, ratio, and relative risk with 95% confidence intervals using a random effect model.A total of 2 RCTs were included in the combined analysis. There were no significant differences in the main outcome indicators (modified Rankin scale score at 90 days, successful postoperative reperfusion rate) or the incidence of adverse events (90-day mortality and symptomatic 2 This is a provisional file, not the final typeset article intracranial hemorrhage) between the NCCT±CTA and CTP groups. The time from last seemed well to puncture was significantly shorter in the NCCT±CTA group than in the CTP group (SMD: -0.14; 95% CI: -0.24, -0.04). Among these, age (OR: 0.96; 95% CI: 0.94, 0.98), ASPECTS (OR: 1.18; 95% CI: 1.12, 1.24), NIHSS score (OR: 0.90; 95% CI: 0.89, 0.91) and diabetes (OR: 0.69; 95% CI: 0.54, 0.88) were associated with 90-day independent functional outcome.Conclusions: These findings suggest that the choice of NCCT±CTA (without CTP) for the assessment of mechanical thrombectomy within 6-24 hours of LVO in the anterior circulation is not significantly different from CTP, instead the choice of NCCT±CTA significantly reduces the time from onset to arterial puncture.